2018
DOI: 10.1002/jpen.1041
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Assessing Prognostic Nutrition Index in Patients With Rectal Cancer Who Receive Preoperative Chemoradiotherapy

Abstract: Pretreatment PNI could be useful in evaluating and managing patients with rectal cancer who undergo CRT followed by curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…Low PNI has been found to be associated with a poor prognosis of some solid cancers. [7][8][9][10][11][12] However, the role of PNI in initially diagnosed NSCLC patients with bone metastasis remains unclear. Our retrospective study aims to evaluate the prognostic role of PNI in initially diagnosed NSCLC patients with bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Low PNI has been found to be associated with a poor prognosis of some solid cancers. [7][8][9][10][11][12] However, the role of PNI in initially diagnosed NSCLC patients with bone metastasis remains unclear. Our retrospective study aims to evaluate the prognostic role of PNI in initially diagnosed NSCLC patients with bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identi cation of a novel biomarker that could predict prognosis and tumor response is vital. Recently, studies have shown that CEA [7], FARI [20], and PNI [21] are practical predictors of survival and tumor response in LARC patients who underwent radical surgery after NCRT. Hence, we veri ed the prognostic role of these parameters and established a CFP scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic nutritional index (PNI), based on the albumin level and lymphocyte count, is another widely used biomarker that combines in ammatory and nutritional parameters. Okugawa et al [21] analyzed rectal cancer patients who underwent NCRT and demonstrated that PNI could predict survival and tumor response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has previously demonstrated that various preoperative biomarkers reflecting host nutrition status, such as prognostic nutrition index (PNI), lymphocyte-C-reactive protein ratio, albumin-globulin ratio and psoas muscle index (PMI), could be used as predictive indicators for postoperative recurrence, especially in malignancies [11][12][13][14][15][16][17][18]. In addition, the advanced lung cancer inflammation index (ALI) is a newly proposed nutrition marker, and is defined by the combination of body mass index (BMI) and the level of preoperative serum albumin (Alb) and neutrophil-tolymphocyte ratio (NLR) [19,20].…”
Section: Introductionmentioning
confidence: 99%